THE EFFECTIVENESS OF FLUTINEX IN THE TREATMENT OF SEASONAL ALLERGIC RHINITIS (The New Uzbekistan Journal of Medicine, 2025)
Seasonal allergic rhinitis is one of the most common diseases in the Republic of Uzbekistan. The aim of our study was to evaluate the effectiveness of Flutineks in the treatment of this disease. The study included 60 patients aged 18 to 45 years. When Flutineks and Teriks (Cetirizine) were used together, a significant reduction in symptoms such as nasal congestion, sneezing, and rhinorrhea was observed. The study results demonstrated the high clinical efficacy of Flutineks and its important role as an intranasal corticosteroid in the treatment of allergic rhinitis.